<span>Simplifying
4(y + -3) = 6(y + 2)
Reorder the terms:
4(-3 + y) = 6(y + 2)
(-3 * 4 + y * 4) = 6(y + 2)
(-12 + 4y) = 6(y + 2)
Reorder the terms:
-12 + 4y = 6(2 + y)
-12 + 4y = (2 * 6 + y * 6)
-12 + 4y = (12 + 6y)
Solving
-12 + 4y = 12 + 6y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-6y' to each side of the equation.
-12 + 4y + -6y = 12 + 6y + -6y
Combine like terms: 4y + -6y = -2y
-12 + -2y = 12 + 6y + -6y
Combine like terms: 6y + -6y = 0
-12 + -2y = 12 + 0
-12 + -2y = 12
Add '12' to each side of the equation.
-12 + 12 + -2y = 12 + 12
Combine like terms: -12 + 12 = 0
0 + -2y = 12 + 12
-2y = 12 + 12
Combine like terms: 12 + 12 = 24
-2y = 24
Divide each side by '-2'.
y = -12
Simplifying
y = -12</span>
Answer:
80,000 people will vote. I'm pretty sure
Step-by-step explanation:
You first divided 200,000 by 10 then multiply it by 4 and you get 80,000. You're welcome, if its right.
In your calculator, input arcsin(7/12). Make sure that your calculator is in degree mode. The answer is 35.69 degrees.
Answer:
102 students
Step-by-step explanation:
Note that 65% and 71% are both 1 standard deviation from the mean (71%). According to the empirical rule, 68% of scores lie within 1 std. dev. of the mean.
68% of 150 students would be 0.68(150 students) = 102 students
Answer: HL
Step-by-step explanation:
The hypotenuse is actually a shared side of the two triangles. (The line segment that crosses the middle of the rectangle) The hypotenuse is the side of a triangle opposite the 90 degree angle. We can use this for hypotenuse congruency. The diagram also shows the shorter legs of the two triangles are congruent. (The legs refer to the sides that make the 90 degree angle)
So we have hypotenuse congruency and leg congruency.
=HL